2010
DOI: 10.1111/j.1524-4741.2009.00850.x
|View full text |Cite
|
Sign up to set email alerts
|

Flat Epithelial Atypia and Atypical Ductal Hyperplasia: Carcinoma Underestimation Rate

Abstract: This study was carried out to determine the underestimation rate of carcinoma upon surgical biopsy after a diagnosis of flat epithelial atypia and atypical ductal hyperplasia and 11-gauge vacuum-assisted breast biopsy. A retrospective review was conducted of 476 vacuum-assisted breast biopsy performed from May 2005 to January 2007 and a total of 70 cases of atypia were identified. Fifty cases (71%) were categorized as pure atypical ductal hyperplasia, 18 (26%) as pure flat epithelial atypia and two (3%) as con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 35 publications
3
23
1
Order By: Relevance
“…These authors also noted that tumors excised after NCB diagnosis of pure FEA had favorable prognostic factors. 22 Moreover, Ingegnoli et al 23 have reported similar results where 20% of pure FEA were malignant (3/15).…”
supporting
confidence: 59%
“…These authors also noted that tumors excised after NCB diagnosis of pure FEA had favorable prognostic factors. 22 Moreover, Ingegnoli et al 23 have reported similar results where 20% of pure FEA were malignant (3/15).…”
supporting
confidence: 59%
“…When considering the stereotactically guided biopsies in our sample, the frequency of pure flat epithelial atypia increases to 9%, whereas pathologic and radiologic series have reported the frequency of pure flat epithelial atypia ranging from 3.6% to 7.6% [10][11][12][13]. Radiologic description of flat epithelial atypia is scant in the literature [14,15].…”
Section: Discussionmentioning
confidence: 80%
“…There are two histological types: one with the cytological features of low-grade ductal carcinoma in situ (DCIS) with insufficient architectural atypia, and the other called 'mini-DCIS' with similar cytology and architectural atypia but of a smaller size (<2 mm) [3]. It is difficult to histologically differentiate between ADH and DCIS [4].…”
Section: Discussionmentioning
confidence: 99%
“…The reported rate of underestimation of carcinoma in CNB-diagnosed ADH is as high as 48% [3-8]. Therefore, complete surgical excision is generally recommended for ADH lesions diagnosed using CNB.…”
Section: Introductionmentioning
confidence: 99%